You are on page 1of 9

# GIKPKC7 94107 The Tangent and the Derivative Page 1

Introduction
14/5/98
Terms:
Asymptote The line were the locus will never touch
Continuous Unbroken locus
Discontinuous Broken locus
Derivative Equal to the gradient E.g. f’(x) = 2.x (Sub ‘x’ to get gradient at x)

Limits:
 To find the limit for any thing, except , when the pronumeral is the denominator:
First factorise (If not done, the answer in undefined), cancel out sub the limit in.
 To find the limit for : divide by the highest power in each, and:
1
Equation: lim  0
x  x

## Note: The factorised answer is not the correct

equation so if you need to draw the locus use
the original equation.

##  To graph the equation use limits if unsure plot some points

E.g. (1) Graph y = 2x
Asymptote
A As x  , y   1
As x   , y  0

Finding limit

lim 2 x = 2
x  
= 0 (i.e. Limit (Aymptote) at
y = 0 when, x  )

x 2  5 .x
E.g. (2) lim
x0 x

x 2  5.x x x  5
A lim  lim
x0 x x0 x
lim
= x 0 x  5
Sub, x = 0
= 5 (i.e. limit at y = 5 when, x  0)

## Luke Cole Page 1

GIKPKC7 94107 The Tangent and the Derivative Page 2

Continuity:
 If discontinuous use limits to find the value that the locus approaches at that point.
 If the locus can be draw without taking pen off paper, it’s continuous.
x2  1
E.g. y
x 1
(1, 2)
A Here, x  1
 Discontinuous
So, lim
x2  1
 lim
 x  1 x  1
x1 x  1 x 1 x 1
= lim x  1
x 1
=2

## Luke Cole Page 2

GIKPKC7 94107 The Tangent and the Derivative Page 3

## Secants and Tangents

15/5/98
y =x2 y f(x)
A(3, 9) A[x + h, f(x + h)]

x x

## B(1, 1) B[x, f(x)]

Key
Secant
Locus
Tangent (Secant when two points become so close that it becomes
one point)

## Gradient of AB (First Principles):

 When using this formula it is called Differentiation
 When differentiating a function use f’(x)
d (Vertical Axis )
 When differentiating anything else use
d (Horizontal Axis )
f x  h  f x 
Equation: M AB  lim
h0 h

E.g. (1) Differentiate from first principles to find the gradient of the tangent to the
curve f(x) = x2 + 3 at any point.

A f’(x) = lim
x  h   3  x
2 2
3 
h 0 h
h2.x  h 
= lim
h 0 h
= 2.x

E.g. (2) Differentiate from first principles y = x3 – x, and find the tangent when
x = 2.

A
dy
 lim
 3
 
 x  h   x  h   x 3  x 
dx h 0 h
2
= lim 3.x  1
h 0

## Luke Cole Page 3

GIKPKC7 94107 The Tangent and the Derivative Page 4

dy
 32  1
2
dx
m = 15

Alternatively

dy
When, y = xn Then,  n .x n 1
dx

dy
When, y = f(x)  g(x) Then, = f’(x)  g’(x)
dx

dy
When, y = C Then, 0
dx

## Luke Cole Page 4

GIKPKC7 94107 The Tangent and the Derivative Page 5

Further Differentiating
15/5/98
Chain Rule:
d d dy
Equation:  
dx dy dx

Proof:
Let, y = f(u)
Let, u = g(x)
dy f u   f g c 
 lim …(1)
du u g  c  u  g c 
du g  x   g c 
 lim …(2)
dx x c x  c
So add g(x)  g(c): (Note: They cancel so it is still equal)
dy  f  g  x   f  g c  g x   g c  
 lim   
dx x c g x   g c  x  c 
But since u = g(x):
dy  f u   f g c    g  x   g c  
 lim    lim   …(3)
dx u g  c  u  g c   xc x  c 
Sub (1) & (2) into (3):
d d dy
  
dx dy dx
Graphically:
y u y

u x x

## Luke Cole Page 5

GIKPKC7 94107 The Tangent and the Derivative Page 6

dy
E.g. Find of x2 + x.y2 = 4
dx

A So,
d 2
dx

x  x.y2  4 
2.x  x.
dx
 
d 2
y  y 2 .1  0 …(1)
d d dy
Since,  
dx dy dx
d 2
dx
 
y  2. y .
dy
dx
…(2)
Sub (2) into (1)
dy
2.x  2.x. y.  y 2  0
dx
2
dy  y  2.x
 
dx 2.x .y

## Function of a Function Rule (Composite Function Rule):

dy
When, y = [f(x)]n Then, = n[f(x)]n – 1  f’(x)
dx

Proof:
Using, y = 3(6.x2 + 3)7
Let, u = 6.x2 + 3
 y = 3.u7
d d dy
Since,  
dx dy dx
dy
 = 21.u6
dx
dy
 = 12.x
dx
dy
So, = 21(6.x2 + 3)6  12.x
dx

## A f’(x) = 7(6.x2 + 3)6  12.x

Luke Cole Page 6
GIKPKC7 94107 The Tangent and the Derivative Page 7

= 84.x(6.x2 + 3)6

Product Rule:
dy dv du
When, y = u.v Then,  u.  v.
dx dx dx

Proof:
Let, u = f(x)
Let, v = g(x)
dy f  x .g  x   f c .g c 
 lim
dx x c xc
Add f(x).g(c): (Note: They cancel so it is still equal)
dy f  x .g  x   f  x .g c   f  x .g c   f c 
. c
 lim
dx x c xc
dy f  x g  x   g c   g c  f  x   f c 
 lim
dx x c xc
dy f  x g  x   g c  g c  f  x   f c 
 lim  lim
dx x c xc x c x c
dy
= f(c).g’(x) + g(c).f’(x) Since x  c let c be x
dx
dy
= f(x).g’(x) + g(x).f’(x)
dx
dy dv du
  u .  v.
dx dx dx

## E.g. Differentiate y = x3(x + 3)5

dy
A = x3  5(x + 3)4  1 + (x + 3)5  3.x2
dx
dy
= 5.x3(x + 3)4 + 3.x2(x + 3)5
dx

## Luke Cole Page 7

GIKPKC7 94107 The Tangent and the Derivative Page 8

Quotient Rule:
du dv
u v.  u.
When, y  Then, dy dx dx
v  2
dx v
x3
E.g. Differentiate y 
x3

dy  x  3   3.x 2  x 3  1
A 
dx  x  3 2
dy 2.x 3  9.x 2

dx x 2  6.x  9

## Continuity and Differentiability:

 If a derivative exists at a point it is said to be differentiable at that point
 A derivative will exist at a point, if it is continuous at that point

E.g. y = x(x + 2)
Continuous = Yes
Differentiable = Yes

 2

##  A curve may be continuous at a point, but need not be differentiable

E.g. y  x2,x2
Continuous = No
Differentiable = Yes, x  2

## Luke Cole Page 8

GIKPKC7 94107 The Tangent and the Derivative Page 9